Comparative Astigmatism Management Procedures and Postoperative Outcome Analysis: A Literature Review - Muhammad Syifa Habibillah; Yuniati, Shinta Karina (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Astigmatism is a refractive error caused by non-uniformity in the shape of the cornea or lens of the eye, resulting in distortion of vision at various distances. It can result from genetic factors, developmental issues, or injury. While astigmatism can occur at any age, it often emerges in early childhood and may worsen with age, particularly in adulthood. It is most commonly diagnosed in children and young adults.the purpose of this literature review is to compare the effectiveness and safety of the three main approaches to astigmatism treatment: SMILE, Keratoplasty, and other techniques such as AK and TIOL. Methods. A clinical study involving patients with mild to moderate astigmatism. Data on visual measurements, astigmatism measurements, and side effects were collected regularly. The results showed that SMILE has small incisions and lower side effects, but there is still a risk of intraoperative complications. Keratoplasty (especially DALK) offers good visual recovery with few postoperative side effects. TIOL are effective in correcting moderate to high astigmatism with permanent correction, but have a risk of complications. AK is a good option for patients who want to correct astigmatism without more invasive laser surgery. Conclusion. Each method has unique advantages and disadvantages. Choosing the right method can ensure optimal results and clearer vision after surgery.